DAMPAK SHOPPING LIFESTYLE DAN FASHION INVOLVEMENT TERHADAP IMPULSE BUYING KONSUMEN CLARISSA STORE JOMBANG - Husna, Saadatul; Ningsih, Lilis Sugi Rahayu (Pusat Riset dan Inovasi Nasional, 2023)
Analyzing shopping lifestyle and fashion involvement on impulse buying in Clarissa Store Jombang consumers. The advantages of Clarissa Store lie in its fashion that follows trends, reasonable prices, and easy accessibility for consumers to obtain products both offline and online through check-out. Data collection methods include observation, questionnaire distribution, and various literature reviews. The research employs a quantitative approach using multiple linear regression analysis. Sampling was done using non-probability purposive sampling technique, resulting in a sample size of 93 respondents. The research findings indicate: (1) The influenc e of shopping lifestyle on impulse buying in Clarissa Store Jombang consumers, as seen from the latest model indicators, is that consumers are interested in products that are constantly updated according to current trends, which can support their lifestyle, boost self-confidence, and self-recognition. (2) The influence of fashion involvement on impulse buying in Clarissa Store Jombang consumers. Fashion is an important aspect to support consumers' activities since it is no longer solely based on daily style but also an individual's self-image in the public eye. (3) The research results prove that shopping lifestyle and fashion involvement have an impact on impulse buying in Clarissa Store Jombang consumers. Consumers who shop at Clarissa Store Jombang have a spontaneous urge to make unplanned purchases.